AGRICULTURAL MODERNIZATION AND TECHNOLOGICAL PRODUCTION: A RESEARCH WITH THE INCUBATE COMPANY FOR THE TECHNOLOGY CENTER OF SECTIONAL DEVELOPMENT OF VIÇOSA – MG - GALINARI, Tiago Nogueira; BORGES, Ronan Eustáquio; FIÚZA, Ana Louise de Carvalho (Scientia Agraria, 2009)
The production technologies for the field through the promotion of organs, Research Technology Centers, universities and other entities subsidized by the state contribute significantly to the agricultural development of the country. However, many times, some groups and regions are most benefited with some technologies than others. The commodityproducing regions and large farms are, in most cases, the big privileged access to technologies produced and / or financed by the public sector. Located in the Zona da Mata, Minas Gerais region, the city of Viçosa presents lot of rural establishments that use labor-family and is composed predominantly of small farms, making it unlikely the incorporation of new agricultural technologies, as compared the other regions. We performed a search through semi-structured on business incubation and graded by CENTEV / UFV, to identify technologies which are produced by these enterprises and what are its main destinations. It was noted that, as well as most of the agricultural technology produced in Brazil, this is not intended for small rural producers, for establishments that make use of labor-family, and hence in Viçosa and micro. Finally, we must be concluded that state intervention is necessary for the slowdown or revocation of historical and perennial regional inequalities Brazilian.